Adalékok a versaillesi békerendszer történetéhez 1. : a Szerb Királyság Osztrák-Magyar Monarchiával szembeni hadicéljai 1914-1917 = Some details of Versailles peace system 1. : the war objectives of Serbian Kingdom over against the Austro-Hungarian Monarchy 1914-1917 - Gulyás, László (Közép-Európai Közlemények, 2017)
Yugoslavia was born twice (1918, 1945) and split twices (1941, 1991). In Beograd, on the 1st of December, 1918, the fi rst Yugoslavian state was born from separate regions (Croatia, Serbia, South-Hungary, Kosovo, Slovenia, Macedonia, Dalmatia). The main power, and the main actor of this unifi cation was Serbian Kingdom. In our paper we analyze the antecedent of this unifi cation during the First World War. Our essay consists of three parts. In the fi rst part of this essay we analyze the war objectives of Serbian Kingdom how were developed from 1914 to 1917. In the second part of this essay we survey what the Allies states (Great-Britain, France and Russian Empire) think about these war objectives. In the third part of this essay we survey the serb’s war objectives how became common south-slav’s war-objectives by the Corfu Declaration.